Peningkatan Komponen Hasil dan Mutu Benih Dua Varietas Okra melalui Penjarangan Buah - Perwira, Prajna Jaya; Suharsi, Tatiek Kartika; Syukur, Muhamad (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
The fruit thinning treatment is known to be able to improve seed quality. This research aimed to increase the yield component and seed quality on two okra varieties (Naila and Zahira) through fruit thinning. This experiment was conducted in May until September 2018 at the Leuwikopo IPB Field, Postharvest Laboratory, and Seed Testing Laboratory, Department of Agronomy and Horticulture, Faculty of Agriculture, Bogor Agricultural University. This experiment conducted using the two-factors nested design, which is a fruit thinning factor as subplots consisting of five levels and okra varieties consisting of two levels. The results showed that the fruit thinning factor influenced the parameters of yield components (fruit length and weight per fruit) and 1,000 seeds weight. The variety factor influenced most of the yield component parameters and seed quality in okra plants. The thinning treatment of the first two fruits and elimination of one fruit interval resulted in the highest physical quality of seed based on 1,000 seeds weight (67.99 g). Keywords: 1,000 seed weight, physical quality